Beyond Green Hype: Attitude, Trust & Ethics For E-Motors - Maha Wiradharma, Putu; Muna, Nilna (Dinasti Publisher, 2025)
This research aims to fill the gap in inconsistent findings on the relationship between green attitude and green purchase intention using the Theory of Planned Behavior (TPB) approach by adding green trust and environmental ethics as mediating variables. Data were collected through a survey of 200 potential respondents and analyzed using structural equation modeling (SEM) based on partial least squares (PLS). Positive and significant results were found in the relationship between green attitude, green trust, environmental ethics, and electric motorcycle purchase intention. In addition, green trust and environmental ethics were able to mediate the relationship between green attitude and electric motorcycle purchase intention. These findings provide insights for electric motorcycle manufacturers and policymakers to improve strategies that promote positive environmental attitudes and trust in green products, ultimately encouraging sustainable consumer behavior. This research provides an original contribution and fills a knowledge gap by combining the concepts of green trust and environmental ethics in the Theory of Planned Behavior (TPB) model, which has not been widely studied in Indonesia. In addition, this study introduces a new model that can be the basis for future research in sustainability and green marketing.